Coating composition, film, and laminate

JP7635975B2Active Publication Date: 2025-02-26NAT INST FOR MATERIALS SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021049328
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-02-26
Estimated Expiration
2041-03-24

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、優れた強度と優れた自己修復性能とを併せ持った塗膜を形成可能なコーティング用組成物が提供できる。また、本発明によれば、膜、及び、積層体も提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635975000001
    Figure 0007635975000001
  • Figure 0007635975000002
    Figure 0007635975000002
  • Figure 0007635975000003
    Figure 0007635975000003
Patent Text Reader

Abstract

To provide a composition for coating that can form a coating layer having both of excellent strength and excellent self-repairing ability.SOLUTION: A composition for coating comprises a polymer compound with a number average molecular weight of 5.0×105-1.0×107, an ionic liquid, and a solvent, with the mass ratio of the content of the polymer compound to the content of the ionic liquid being 0.15 or more and less than 1.00.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition, a film, and a laminate. [Background technology]

[0002] Composite films having a coating layer containing an ionic liquid are known. Patent Document 1 describes "a composite film having a support and a surface coating layer, the surface coating layer containing 0.05% by mass to 10% by mass of an ionic liquid relative to the total solid content in the surface coating layer." [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-77786 A Summary of the Invention [Problem to be solved by the invention]

[0004] The surface coating layer of the composite film described in Patent Document 1 has insufficient self-repairing performance and has room for improvement. Therefore, an object of the present invention is to provide a coating composition capable of forming a coating film having both excellent strength and excellent self-repairing performance. Another object of the present invention is to provide a film and a laminate. [Means for solving the problem]

[0005] As a result of extensive investigations aimed at achieving the above object, the present inventors have found that the above object can be achieved by the following configuration.

[0006] [1] Number average molecular weight is 5.0×10 5 ~1.0×10 7a polymer compound represented by the formula (I), an ionic liquid, and a solvent, wherein the ratio of the content of the polymer compound to the content of the ionic liquid on a mass basis is 0.15 or more and less than 1.00. [2] Number average molecular weight is 1.4×10 6 The coating composition according to [1] above. [3] The coating composition according to [1] or [2], wherein the ratio is 0.65 or less. [4] The coating composition according to any one of [1] to [3], wherein the polymer compound is at least one selected from the group consisting of poly(meth)acrylic acid, poly(meth)acrylic acid esters, poly(meth)acrylamide, and poly(meth)acrylonitrile. [5] The coating composition according to [4], wherein the polymer compound is poly(meth)acrylic acid or a poly(meth)acrylic acid ester. [6] The coating composition according to [4], wherein the polymer compound is polymethacrylic acid or a polymethacrylic acid ester. [7] The coating composition according to any one of [1] to [6], wherein the ionic liquid is an ionic liquid represented by the below-mentioned formula 8. [8] R in Equation 8 below 83 , and R 84 each independently represents a perfluoroalkyl group. [9] In the following formula 8, R 83 , and R 84 The coating composition according to [8], wherein

[10] The coating composition according to any one of [1] to [9], wherein the solvent is at least one solvent selected from the group consisting of ketone-based solvents, aromatic hydrocarbon-based solvents, halogen-based solvents, and ether-based solvents.

[11] The coating composition according to

[10] , wherein the solvent is at least one solvent selected from the group consisting of acetone, toluene, chloroform, dichloromethane, and tetrahydrofuran.

[12] A film formed from the coating composition according to any one of [1] to

[11] .

[13] A laminate having a substrate and the film of

[12] formed on the substrate. Effect of the Invention

[0007] According to the present invention, there is provided a coating composition capable of forming a coating film having both excellent strength and excellent self-repairing performance. Further, according to the present invention, there is also provided a film and a laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0009] In addition, in this specification, "(meth)acrylate" refers to both or either of acrylate and methacrylate, "(meth)acrylic" refers to both or either of acrylic and methacrylic, and "(meth)acryloyl" refers to both or either of acryloyl and methacryloyl.

[0010] [Composition] The composition according to the embodiment of the present invention has a number average molecular weight of 5.0×10 5 ~1.0×10 7 The coating composition comprises a polymer compound represented by the formula (I), an ionic liquid, and a solvent, and the ratio of the content of the polymer compound to the content of the ionic liquid based on mass (polymer compound / ionic liquid, hereinafter also referred to as "P / I ratio") is 0.15 or more and less than 1.00. Each component of the present invention will be described in detail below.

[0011] <Polymer compounds> The coating composition has a number average molecular weight of 5.0×10 5 ~1.0×10 7 The number average molecular weight of the polymer compound is 5.0×10 5 If it is less than 1.0×10, the strength of the resulting coating film will be insufficient. 7 If it exceeds this value, the handling properties become insufficient.

[0012] From the viewpoint of obtaining a coating film having a more excellent effect of the present invention, the number average molecular weight of the polymer compound is 9.0×10 5 More than 1.3×10 is preferable. 6 More preferably, 1.4×10 6 The above is more preferable. The number average molecular weight of the polymer compound is 1.4×10 6 If the number average molecular weight is more than 100%, the resulting coating film has better self-repairing properties. The number average molecular weight of the polymer compound means a value measured by the method described in the Examples.

[0013] The degree of polymerization of the polymer compound is not particularly limited, but is preferably at least 5,000, more preferably at least 9,000, and even more preferably at least 14,000. The upper limit is not particularly limited, but is preferably 100,000 or less.

[0014] The content of the polymer compound in the coating composition is adjusted so that the P / I ratio is 0.15 or more and less than 1.00. If the P / I ratio is less than 0.15, the strength of the resulting coating film will be insufficient, whereas if the P / I ratio is 1.00 or more, the self-repairing performance will be insufficient. When the P / I ratio is 0.65 or less, the resulting coating film has better self-repairing properties, and when the ratio is 0.40 or more, the resulting coating film has better effects according to the present invention.

[0015] In this specification, the P / I ratio is calculated in different ways depending on the production method of the coating composition described below. When a coating composition is prepared by mixing a polymer compound, an ionic liquid, and a solvent, the contents are calculated based on the charge ratios. When a coating composition is prepared by polymerizing a radically polymerizable compound in an ionic liquid to obtain a polymer compound and adding a solvent, the amount of the radically polymerizable compound charged is multiplied by the conversion rate of the radically polymerizable compound to calculate the content of the polymer compound in the obtained ion gel (composite of the polymer compound and the ionic liquid), and then the above P / I ratio is calculated.

[0016] The content of the ionic liquid in the entire coating composition is not particularly limited as long as the P / I ratio falls within a predetermined range. For example, when the total mass of the composition is taken as 100 mass%, the content is preferably 1 to 20 mass%. The coating composition may contain one type of polymer compound alone or two or more types. When the coating composition contains two or more types of polymer compounds, the total content is preferably within the above numerical range.

[0017] As the polymer compound, a known polymer compound can be used, but from the viewpoint of obtaining a coating composition having a more excellent effect of the present invention, a polymer compound obtained by polymerizing a radically polymerizable compound is preferred.

[0018] Examples of such radical polymerizable compounds include carboxy group-containing compounds such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid, as well as esters thereof; amide compounds such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; and cyano(meth)acrylate compounds such as (meth)acrylonitrile.

[0019] As the polymer compound, from the viewpoint of obtaining a coating composition having a more excellent effect of the present invention, at least one selected from the group consisting of poly(meth)acrylic acid, poly(meth)acrylic acid esters, poly(meth)acrylamide, and poly(meth)acrylonitrile is preferable, poly(meth)acrylic acid or poly(meth)acrylic acid esters is more preferable, and polymethacrylic acid or polymethacrylic acid esters is even more preferable.

[0020] <Ionic liquid> As used herein, ionic liquid refers to a non-volatile salt formed by the combination of a cation and an anion, the salt having a melting point of 25° C. or less under atmospheric pressure.

[0021] The cation constituting the ionic liquid is preferably at least one selected from the group consisting of organic cations and metal complex cations, and preferably contains an organic cation or is preferably made of an organic cation. In this specification, the organic cation means a cation that does not contain a metal atom and has at least one carbon atom.

[0022] The organic cation is not particularly limited, but examples thereof include onium ions. More specifically, ammonium ions (e.g., R A 4N + ), iminium ions (e.g., R B 2C=N + R 1 2), sulfonium ions (e.g., R A 3S + ), oxonium ions (e.g., R A 2O + ), phosphonium ion (representative structure: R A 4P + ), and iodonium ions (e.g., R A 2I + ) etc. In the above formulas, R AR represents a substituent such as an alkyl group, an aryl group, or a heterocyclic group. B represents a hydrogen atom or a monovalent substituent. 1 , multiple R in molecule B , or R in the molecule A and R B may be bonded to each other to form a ring. A , or two R B together form a double bond group (e.g., =O, =S, =NR B ) may be formed.

[0023] The metal complex cation is not particularly limited, and examples thereof include ferrocene-based, cobaltocene-based, ruthenium-based, and solvated ions of lithium, sodium, and the like, whose high Lewis acidity is lowered by coordination with crown ether or the like.

[0024] Other forms of cations include ammonium ions, pyrrolidinium ions, pyridinium ions, piperidinium ions, oxazolium ions, oxazolinium ions, imidazolium ions, thiazolium ions, and phosphonium ions.

[0025] Ammonium ion An example of the ammonium ion is a cation represented by the following formula 1. [ka]

[0026] In formula 1, R 1 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 1 may be the same or different. 1 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0027] Pyrrolidinium ion An example of the pyrrolidinium ion is a cation represented by the following formula 2. [ka]

[0028] In formula 2, R 2 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 2 may be the same or different. 2 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0029] Piperidinium ion An example of the piperidinium ion is a cation represented by the following formula 3. [ka]

[0030] In formula 3, R 3 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 3 may be the same or different. 3 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0031] Pyridinium ion An example of the pyridinium ion is a cation represented by the following formula 4. [ka]

[0032] In formula 4, R 4 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 4 may be the same or different. 4The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0033] Imidazolium ion An example of the imidazolium ion is a cation represented by the following formula 5. [ka]

[0034] In formula 5, R 5 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 5 may be the same or different. 5 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0035] The phosphonium ion may, for example, be a cation represented by the following formula 6: [ka]

[0036] In formula 6, R 6 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 6 may be the same or different. 6 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may contain a hetero atom.

[0037] The anion constituting the ionic liquid is not particularly limited, and a known anion can be used. Among them, the anion is preferably an anion containing a halogen atom. The halogen atom is not particularly limited, but is preferably fluorine or bromine, and more preferably fluorine.

[0038] The anion containing a halogen atom is not particularly limited, and examples thereof include anions represented by the following formula 7. [ka]

[0039] In formula 7, R 7 represents a halogenated alkyl group, and preferably a fluorinated alkyl group. 7 may be the same or different. 7 may be linked to each other to form a ring.

[0040] Specific examples of the anion include bis(fluorosulfonyl)imide (FSI), bis(trifluoromethanesulfonyl)imide (TFSI), bis(pentafluoroethylsulfonyl)imide (BETI), N,N-bis(nonafluorobutanesulfonyl)imide (NFSI), and N,N-hexafluoropropane-1,3-disulfonylimide (cTFSI).

[0041] As the ionic liquid, an ionic liquid represented by the following formula 8 is preferred from the viewpoint of obtaining a coating composition having a more excellent effect of the present invention.

[0042] [ka]

[0043] In formula 8, R 81 , and R 82 R each independently represents an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 4 carbon atoms. 81 The number of carbon atoms in the alkyl group of R 82 may have the same or different numbers of carbon atoms, but preferably have different numbers of carbon atoms.

[0044] R 83 , and R 84each independently represents a monovalent organic group and may be the same or different. That is, the structure of the anion may be symmetric or asymmetric.

[0045] As the monovalent organic group, for example, a substituted or unsubstituted hydrocarbon group which may have a heteroatom is preferable, and in order to obtain an ion gel having a more excellent effect of the present invention, R 83 , and R 84 are each independently preferably a halogenated alkyl group, and more preferably a perfluoroalkyl group. The number of carbon atoms in the halogenated alkyl group is not particularly limited, but is preferably 1 to 10, more preferably 1 to 8, and even more preferably 1 to 6.

[0046] The perfluoroalkyl group is preferably at least one group selected from the group consisting of -C4F9, -C3F7, -C2F5, and -CF3, and from the viewpoint that the resulting coating film has superior self-repairing performance, -CF3 (trifluoromethyl group) is more preferable.

[0047] The content of the ionic liquid in the coating composition is not particularly limited as long as the P / I ratio is within a predetermined range, but is preferably 5 to 30 mass% based on the total mass of the coating composition. The coating composition may contain one type of ionic liquid alone, or may contain two or more types. When the coating composition contains two or more types of ionic liquids, the total content is preferably within the above numerical range.

[0048] <Solvent> The solvent contained in the coating composition is preferably highly compatible with the polymer compound and the ionic liquid. Examples of the solvent include water, an organic solvent, and a mixture thereof. From the viewpoint of providing the coating composition with superior handling properties, the solvent is preferably an organic solvent.

[0049] Examples of the solvent include water; alcohol-based solvents such as methanol, ethanol, propanol, ethylene glycol, glycerin, and propylene glycol monomethyl ether; acids such as acetic acid; ketone-based solvents such as acetone, methyl ethyl ketone, and cyclohexanone; amide-based solvents such as formamide, dimethylacetamide, and N-methylpyrrolidone; nitrile-based solvents such as acetonitrile and propionitrile; ester-based solvents such as methyl acetate and ethyl acetate; carbonate-based solvents such as dimethyl carbonate and diethyl carbonate; aromatic hydrocarbon-based solvents such as benzene, toluene, and xylene; halogen-based solvents such as chloroform and dichloromethane; ether-based solvents such as diethyl ether and tetrahydrofuran; glycol-based solvents; amine-based solvents; and thiol-based solvents.

[0050] Among these, ketone-based solvents, aromatic hydrocarbon-based solvents, halogen-based solvents, and ether-based solvents are preferred, and specifically, acetone, toluene, chloroform, dichloromethane, tetrahydrofuran, and the like are preferred.

[0051] The content of the solvent in the coating composition is not particularly limited, but is generally preferably 10 to 90% by mass based on the total mass of the coating composition, in that a coating composition having a more excellent effect of the present invention can be obtained. The coating composition may contain one type of solvent alone, or may contain two or more types. When the coating composition contains two or more types of solvents, the total content is preferably within the above numerical range.

[0052] <Other ingredients> The coating composition of the present invention may contain other components within the scope of the effects of the present invention, so long as it contains the above-mentioned components, such as fillers, pigments, antisettling agents, defoamers, UV absorbers, antioxidants, surface conditioners, viscosity modifiers, leveling agents, dispersants, and preservatives.

[0053] [Method of producing coating composition] The method for producing the coating composition is not particularly limited, and a known method can be used. For example, a method of dissolving a polymer compound in a solvent to obtain a polymer compound solution, diluting an ionic liquid with the solvent to obtain an ionic liquid dilution, and mixing the polymer compound solution and the ionic liquid dilution to obtain the coating composition can be mentioned.

[0054] From the viewpoint of obtaining a more uniform coating composition in a shorter time even when the polymer compound has a high number average molecular weight, a method for producing a coating composition having the following steps is preferred.

[0055] (Preferred embodiment of the method for producing the coating composition) A composition comprising a radical polymerizable compound (M), a radical polymerization initiator (RI), and an ionic liquid (I), in which the mass ratio of the content of the radical polymerization initiator to the content of the radical polymerizable compound (radical polymerization initiator / radical polymerizable compound, hereinafter also referred to as the "RI / M ratio") is 5×10 -5 ~2×10 -3 and preparing a polymerization composition (pre-gel solution) having a mass ratio of the content of the radical polymerizable compound to the content of the ionic liquid (radical polymerizable compound / ionic liquid, hereinafter also referred to as "M / I ratio") of 0.15 or more and less than 1.00 (polymerization composition preparation step). A step of polymerizing a radically polymerizable compound in a polymerization composition to generate a polymer compound having a number average molecular weight of 500,000 to 10,000,000, and obtaining an ion gel containing the polymer compound and an ionic liquid (polymerization step). A process of adding a solvent to the ion gel to obtain a coating composition (dissolving process)

[0056] According to the above-mentioned production method, a uniform ion gel containing an ionic liquid and a polymer compound can be synthesized in a shorter time, and the coating composition obtained by diluting the ion gel also has excellent uniformity and requires less time to produce.

[0057] In general, when attempting to obtain a polymer compound having a number average molecular weight of 500,000 (preferably 900,000) or more, it has been thought that simply reducing the content of the radical polymerization initiator in the polymerization composition does not sufficiently increase the conversion rate of the radical polymerizable compound (monomer), making it impossible to obtain a compound with the desired high molecular weight. However, according to the study by the present inventors, it was surprisingly found that in an ionic liquid, the RI / M ratio can be increased to 5×10 -5 ~2×10 -3 It has been found that by doing so, it is possible to obtain a uniform ion gel containing a polymer compound having a desired molecular weight and an ionic liquid. The present production method has been completed based on the above-mentioned findings.

[0058] ·Polymerization composition preparation process The polymerization composition used in the present production method contains a radical polymerizable compound, a radical polymerizable compound, and an ionic liquid. Each component contained in the polymerization composition will be described in detail below.

[0059] (Radical polymerizable compound) The radically polymerizable compound is a compound having at least one radically polymerizable group in the molecule, and is preferably a compound having one radically polymerizable group in the molecule.

[0060] Examples of the radically polymerizable group include groups having an ethylenically unsaturated bond such as a vinyl group, a (meth)acryloyl group, and an allyl group. Of these, a (meth)acryloyl group is preferred.

[0061] The molecular weight of the radically polymerizable compound is not particularly limited, but is generally preferably 50 or more and 1,000 or less.

[0062] Examples of the radically polymerizable compound include carboxy group-containing compounds such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid, as well as esters thereof; amide compounds such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, and N-methylolpropane(meth)acrylamide; and cyano(meth)acrylate compounds such as (meth)acrylonitrile.

[0063] The radical polymerizable compound is preferably at least one compound selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid esters, (meth)acrylamide, and (meth)acrylonitrile, and more preferably (meth)acrylic acid or (meth)acrylic acid esters.

[0064] The content of the radical polymerizable compound in the polymerization composition is RI / M ratio is 5×10 -5 ~2×10 -3 The RI / M ratio is adjusted to 1×10 -3 Less than 5×10 is preferable. -4 Less than 3×10 is preferable. -4 It is more preferable that the above ratio is rounded to one significant digit.

[0065] RI / M ratio is 5×10 -5 At this level or higher, the conversion rate of the radical polymerizable compound is further improved. When the conversion rate is improved, the radical polymerizable compound is less likely to remain in the resulting ion gel, and defects are less likely to occur on the surface of the coating film formed using the coating composition. On the other hand, the RI / M ratio is 2×10 -3 If it is less than this, the degree of polymerization will be higher and the resulting coating will have better strength.

[0066] In addition, the RI / M ratio is 1×10 -3 If it is less than 5 × 10, the number average molecular weight of the polymer compound tends to be large, which is preferable. -4 When the molecular weight is less than 1, the number average molecular weight of the polymer compound tends to become larger, which is preferable.

[0067] The polymerization composition may contain one type of radical polymerizable compound alone or two or more types. When the polymerization composition contains two or more types of radical polymerizable compounds, the total content is preferably within the above numerical range.

[0068] (Radical polymerization initiator) The radical polymerization initiator contained in the polymerization composition includes a thermal radical polymerization initiator and a photoradical polymerization initiator.

[0069] Examples of the thermal radical polymerization initiator include peroxides such as t-butyl peroxybenzoate, di-t-butyl peroxide, cumene perhydroxide, acetyl peroxide, benzoyl peroxide, and lauroyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and azobiscyclohexanecarbonitrile.

[0070] Examples of the photoradical polymerization initiator include 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 2,2-dimethoxy-1,2-diphenylethan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide.

[0071] The content of the radical polymerization initiator in the polymerization composition is preferably adjusted so that the RI / M ratio is within a predetermined range, and is preferably 0.0001 to 3 parts by mass, relative to 100 parts by mass of the total content of the radical polymerizable compound and the content of the ionic liquid in the polymerization composition. The polymerization composition may contain one type of radical polymerization initiator alone or two or more types. When the polymerization composition contains two or more types of radical polymerization initiators, the total content is preferably within the above numerical range.

[0072] (Ionic Liquid) The ionic liquid contained in the polymerization composition is the ionic liquid contained in the coating composition, and therefore the same ionic liquid as the ionic liquid described as a component of the coating composition can be used, and the preferred forms are also the same.

[0073] The content of the ionic liquid in the polymerization composition is adjusted so that the M / I ratio is 0.15 or more and less than 1.00. When the M / I ratio is 0.65 or less, the resulting coating film has better self-repairing properties. Also, when the M / I ratio is 0.40 or more, the resulting coating film has better effects of the present invention.

[0074] The polymerization composition can be prepared by mixing the components. The mixing method and order are not particularly limited, but an example of the method is mixing a radical polymerizable compound and a radical polymerization initiator, and then mixing an ionic liquid.

[0075] ·Polymerization process The polymerization step is a step of polymerizing a radically polymerizable compound in a polymerization composition to produce a polymer compound having a number average molecular weight of 500,000 to 10,000,000, and obtaining an ion gel containing the polymer compound and an ionic liquid.

[0076] The method for polymerizing the radically polymerizable compound in the composition to produce a polymer compound having a number average molecular weight of 500,000 to 10,000,000 is not particularly limited, and any known method may be appropriately selected depending on the type of radical polymerization initiator. For example, when the composition contains a thermal radical polymerization initiator, it may be heated in an inert gas atmosphere at a temperature of room temperature to 130° C. for 1 to 72 hours.

[0077] The conversion rate (%) of the radical polymerizable compound is not particularly limited, but from the viewpoint of obtaining an ion gel having a more excellent effect of the present invention, it is preferably 70% or more, more preferably more than 70%, more preferably 90% or more, and particularly preferably more than 90%. The upper limit is generally 100% or less.

[0078] The number average molecular weight of the polymer compound obtained by radical polymerization is 5.0 × 10 5 ~1.0×10 7 From the viewpoint of obtaining a coating composition having a more excellent effect of the present invention, the number average molecular weight of the polymer compound is 9.0 × 10 5 More than 1.3×10 is preferable. 6 More preferably, 1.4×10 6 The number average molecular weight of the polymer compound is a value measured by the method described in the Examples.

[0079] The degree of polymerization of the polymer compound is not particularly limited, but is preferably at least 5,000, more preferably at least 9,000, and even more preferably at least 14,000. The upper limit is not particularly limited, but is preferably 100,000 or less.

[0080] When the radically polymerizable compound is polymerized, a polymer compound is produced, and an ion gel containing the polymer compound and the ionic liquid is obtained. According to this production method, the radical polymerizable compound is polymerized in a homogeneous polymerization composition containing the radical polymerizable compound, the radical polymerization initiator, and the ionic liquid, and thus the obtained ion gel has excellent uniformity. In addition, by setting the RI / M ratio within a predetermined range, it is possible to simultaneously improve two parameters, namely, the molecular weight and the conversion rate, which have been considered to be in a trade-off relationship in the past. Therefore, the obtained ion gel has excellent uniformity, and as a result, a coating composition having the effects of the present invention is obtained.

[0081] ·Dissolution process The solvent added to the obtained ion gel may be the same as the solvent contained in the coating composition, and the preferred forms are also the same. The method for dissolving the ion gel is not particularly limited, and any known method can be used.

[0082] (Method of using the coating composition) The present coating composition can be used to produce a laminate having a substrate and a film formed on the substrate.

[0083] The method for forming a (coated) film on a substrate using the coating composition is not particularly limited, and a layer of the coating composition may be formed using a known coating method such as a gravure coating method, a reverse coating method, a die coating method, a blade coater, a roll coater, an air knife coater, a screen coater, a bar coater, or a curtain coater, and if necessary, heated and dried to form a film.

[0084] The heating method is not particularly limited, and may be a heat roller, a laminator, a hot plate, or the like. The drying can be carried out by using a stamp, a heat plate, a thermal head, a laser, a blower dryer, an oven, a hot plate, an infrared dryer, a heating drum, or the like.

[0085] The heating temperature is not particularly limited, but is preferably 20 to 120°C, more preferably 20 to 80°C, from the viewpoint of easily suppressing thermal denaturation of each component and the base material.

[0086] The thickness of the coating film is not particularly limited and can be appropriately selected depending on the application, and is preferably, for example, 0.1 μm to 3 mm.

[0087] [Laminate] The laminate is a composite body having a substrate and a (coating) film formed on the substrate using the coating composition already described.

[0088] The material of the substrate is not particularly limited, and metal, resin, glass, etc. can be used, but from the viewpoint of flexibility and weight reduction, examples include resin films formed from glass epoxy, polyester, polyimide, thermosetting polyphenylene ether, polyamide, polyaramid, liquid crystal polymer, etc. in a film shape; glass film; paper; etc. Among these, resin films are preferred from the viewpoint of excellent handling properties.

[0089] The material in the resin film can be any resin that can be molded into a film without any particular limitation, but preferred examples include phenolic resin, epoxy resin, polyimide resin, bismaleimide triazine (BT) resin, polyphenylene ether (PPE) resin, tetrafluoroethylene resin, liquid crystal resin, polyester resin, polyethylene terephthalate, polyethylene naphthalate (PEN), aramid resin, polyamide resin, polyethersulfone, triacetyl cellulose, polyvinyl chloride, polyvinylidene chloride, polyethylene, polypropylene, polystyrene, polybutadiene, and polyacetylene.

[0090] The shape of the substrate may be any shape required for various film substrates, such as a flat surface, a diffusive surface, a concave surface, a convex surface, etc. The thickness of the substrate is preferably 10 μm to 5 mm from the viewpoints of workability during production and molding.

[0091] The film formed on the substrate is as already explained, and the preferred embodiments are also the same.

[0092] (Application) The laminate according to the embodiment of the present invention can be used as an easy-to-maintain exterior wall material, etc., because the coating film formed on the substrate has both excellent self-repairing properties and excellent strength. In addition, the laminate has an antistatic function due to the ionic liquid, and can be used as a more reliable antistatic coated substrate, combined with the excellent self-repairing performance.

[0093] In addition, the present coating composition can also be used as a coating agent for automobiles, etc., a coating agent for forming a protective film for the screen of electronic devices such as mobile phones, etc., and a coating agent for forming a protective film for touch panels, pen input devices, etc. EXAMPLES

[0094] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0095] [Example 1: Preparation of coating composition] Methyl methacrylate (MMA, manufactured by Kanto Chemical) was purified by passing it through a short column of activated alumina to remove the polymerization inhibitor hydroquinone. Next, α,α'-azobisisobutyronitrile (AIBN) powder (0.1 parts by mass) and purified MMA (30 parts by mass) were added to a 5 mL vial and completely dissolved. Next, 70 parts by mass of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C2mIm][TFSI], manufactured by Iolitec) were added to the obtained solution to obtain a uniform and transparent pre-gel solution (corresponding to the polymerization composition).

[0096] Next, the mouth of the vial was sealed with a silicone double cap, and argon was bubbled through the vial using a syringe needle for 10 minutes. The bubbled vial was then placed in an oven heated to 80°C and heated for 24 hours without stirring to obtain an ion gel. The molecular weight of PMMA was 1,740,000, and the degree of polymerization was 4,884. The conversion rate was 98%.

[0097] The content of PMMA (polymethyl methacrylate, corresponding to a polymer compound) in the obtained ion gel was calculated to be 29 parts by mass, calculated by multiplying the content of MMA in the pre-gel solution (30 parts by mass) by 0.98 (conversion rate). As a result, the ratio of the polymer compound content to the ionic liquid content in the ion gel was calculated to be 0.41.

[0098] The obtained ion gel was used to prepare a sample (film) to be used in a tensile test to evaluate the coating strength. Specifically, the ion gel was hot pressed using a 1 mm silicone spacer to obtain Film 1.

[0099] This film 1 has the same components as the coating composition except that it does not contain a solvent, and has the same properties as the coating film obtained using the coating composition. Below, the physical properties of the film obtained by the above method were evaluated as the physical properties of the coating film obtained using the coating composition.

[0100] It was confirmed that a coating composition and a laminate were obtained from the above ion gel. First, acetone was added so that the content of the obtained ion gel was 20 mass %, and the ion gel was dissolved to prepare coating composition 1.

[0101] Next, a laminate was produced using the coating composition 1. The coating composition was applied to a polyethylene terephthalate substrate (thickness 250 μm) using a bar coater (ASONE, 2-9572-13) so that the film thickness after drying was 10 μm, to obtain a composition layer. The obtained composition layer was naturally dried at room temperature to produce a laminate having a coating film (ion gel film) with a thickness of 10 μm.

[0102] [Example 2: Preparation of Membrane 2] Polymethyl methacrylate powder (analytical standard, for GPC, number average molecular weight 1,680,000, 30 parts by mass) was dissolved in dichloromethane to obtain a solution of 10% by mass. Next, the solution was mixed with [C2mIm][TFSI] (70 parts by mass) to obtain coating composition 2.

[0103] The obtained coating composition 2 was poured into a glass petri dish, left to stand at room temperature for 24 hours to volatilize dichloromethane, and further vacuum dried at 120°C for 24 hours to obtain a coating film. The thickness of the coating film was adjusted by hot pressing using a 1 mm thick silicone spacer.

[0104] From the results of Example 1 and Example 2, it became clear that a laminate can be formed using the coating composition regardless of the type of substrate. In the following test, in order to evaluate the physical properties of the coating film formed using the coating composition, a solvent-free ion gel was prepared, processed into a film, and subjected to an evaluation test.

[0105] [Example 3] An ion gel was prepared in the same manner as in Example 1, except that the content of MMA in the pre-gel solution was 40 parts by mass, and the content of the ionic liquid was 60 parts by mass, and thus a membrane 3 was produced. The conversion rate was 99%, the content of PMMA in the ion gel was 40 parts by mass, and the ratio of polymer compound / ionic liquid was 0.67. [Example 4] An ion gel was prepared and a membrane 4 for tensile testing was produced in the same manner as in Example 1, except that bis(pentafluoroethylsulfonyl)imide was used instead of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide as the ionic liquid. The conversion rate was 100%, the content of PMMA in the ion gel was 30 parts by mass, and the ratio of polymer compound / ionic liquid was 0.43.

[0106] [Example 5] An ion gel was prepared and a film 5 for a tensile test was produced in the same manner as in Example 1, except that ethyl methacrylate (EMA) was used instead of MMA. The conversion rate was 99%, the content of polyethyl methacrylate (polymer compound) in the ion gel was 30 parts by mass, and the ratio of polymer compound / ionic liquid was 0.43.

[0107] [Comparative Example 1] The mass ratio of the AIBN content to the MMA content is 3 x 10 -3 An ion gel was prepared and a film C1 for a tensile test was produced in the same manner as in Example 1, except that the above-mentioned procedure was followed. The number average molecular weight of PMMA in the ion gel was 489,000, and the degree of polymerization was 4,884. The conversion rate was 100%, the content of the polymer compound in the ion gel was 30 parts by mass, and the ratio of polymer compound / ionic liquid was 0.43.

[0108] [Comparative Example 2] An ion gel was prepared and a membrane C2 for tensile testing was produced in the same manner as in Example 1, except that the content of MMA in the pregel solution was 50 parts by mass and the content of ionic liquid was 50 parts by mass. The number average molecular weight of PMMA in the ion gel was 1,140,000. The conversion rate was 100%, the content of PMMA in the ion gel was 30 parts by mass, and the ratio of polymer compound to ionic liquid was 0.43.

[0109] [Comparative Example 3] MMA and ethylene dimethacrylate (EGDMA) were purified by passing them through a short column of activated alumina to remove the polymerization inhibitor. Next, AIBN powder, the purified MMA (30 parts by mass), and EGDMA (0.2 mol% relative to MMA) were added to a 5 mL vial and completely dissolved.

[0110] Next, [C2mIm][TFSI] was added (70 parts by mass) to the obtained solution to obtain a uniform and transparent pregel solution. The pregel solution was bubbled with argon for 10 minutes. The bubbled pregel solution was poured into a mold containing a 1 mm thick silicone spacer sandwiched between two glass plates, and heated in an oven heated to 80°C for 24 hours to obtain an ion gel film C3.

[0111] The number average molecular weight of the obtained ion gel could not be measured. This is considered to be because the pre-gel solution contains ethylene dimethacrylate, and the polymer compound in the ion gel has a cross-linked structure. In this specification, the molecular weight of a polymer compound having such a cross-linked structure is defined as "infinite."

[0112] [Conversion (conversion rate)] The conversion of the radical polymerizable compound (unit: %, conversion rate) was measured by the following procedure. Note that the following explanation is for the case where MMA was used as the radical polymerizable compound, but the same applies when EMA was used.

[0113] First, the ion gel was completely dissolved in chloroform-d (manufactured by ACROS ORGANICS, product number 46402-0075) to obtain a solution. Next, the obtained solution was introduced into an NMR (Nuclear Magnetic Resonance) sample tube, and NMR measurement (JEOL, ECZ 400S) was performed at 25°C. From the obtained NMR spectrum, the ratio of the number of residual monomers (radical polymerizable compounds) in the ion gel to the number of MMA units in the polymer was calculated, and the conversion was obtained by the following formula.

[0114]

number

[0115] [Number average molecular weight] The number average molecular weight of the obtained ion gel was measured by GPC. The details of the measurement procedure are as follows.

[0116] (Pretreatment) Each ion gel was purified by reprecipitation. Specifically, the ion gel was dissolved in acetone to a concentration of 1% by mass. Next, the solution was dropped into a large amount of methanol (20 times by volume) to precipitate the polymer (polymer compound). Polymer powder was obtained by suction filtration.

[0117] The polymer powder was again dissolved in acetone, precipitated, and filtered in the same manner, and the obtained polymer powder was vacuum dried for 24 hours at 60° C. Next, the polymer powder was dissolved in an eluent (10 mM LiBr / DMF) to a concentration of 0.1 mass%, and passed through a 0.45 μm syringe filter before being used for measurement.

[0118] (GPC measurement) Device configuration Degasser / JAPAN SPECTRA (DG-2080-53) Pump: JASCO (PU-2080) Interface box / JASCO (LC-Net II / ADC) Column oven / JASCO (CO-4060) RI detector / JASCO (RI-4030) Column: Two Shodex (registered trademark) SB-806M HQ columns connected directly Guard column: Shodex (registered trademark) SB-G 6B

[0119] Standards Type: Polymethyl methacrylate (PMMA) Manufacturer: Shodex (registered trademark) ·Product: STANDARD M-75 Molecular weight range: 2,870~965,000 (7 points)

[0120] Measurement conditions Column temperature: 40℃ ·Flow rate: 1mL / min ·Elution phase: 10mM LiBr / DMF Detection: RI

[0121] analysis A calibration curve was created by linear regression (least squares method) of a third order equation for seven standard samples. Molecular weights exceeding 965,000 were extrapolated using the above calibration curve.

[0122] [Tensile test and self-repair test] (Preparation of test specimens) The ion gel film was punched out with a dumbbell-shaped cutter (manufacturer: Dumbbell Co., Ltd., model: SDMP-1000-D, shape: JIS K-6251-7) to obtain a dumbbell-shaped test piece. The center of the test part of the test piece was cut with a cutter knife, and the cut surfaces were immediately placed in contact with each other and left to stand at room temperature for 6 hours.

[0123] (Tensile test conditions) The tensile test was performed by attaching the test piece to a material testing machine (Shimadzu, AGS-X 100N) at room temperature and at a speed of 10 cm / min.

[0124] (How to calculate the self-repair rate) The fracture energy (integral value of the stress-strain curve) was calculated for the test piece before cutting and the test piece after cutting and repairing, and the ratio of these values ​​expressed as a percentage was defined as the self-repair rate (%). The details of the calculation method are as follows.

[0125] The stress ε and strain σ obtained from the tensile test are expressed as follows:

[0126]

number

[0127] Here, x is the displacement, L is the length of the test area, g(x) is the test force at the displacement x, and A0 is the area of ​​the test area. The fracture energy of the ion gel, E f is expressed by the following equation using σ and ε.

[0128]

number

[0129] Here, ε f represents the fracture strain. From the above, the self-repair rate of the ion gel is calculated by the fracture energy E f,original , and the fracture energy E of the repaired ion gel f,healed It is calculated using the following formula:

[0130]

number

[0131] Table 1 shows the composition of the pre-gel solutions for each Example and Comparative Example. Note that the coating composition for Example 2 was prepared by mixing PMMA, an ionic liquid, and a solvent, so all are indicated with "-". In the "Summary of preparation method" column, "Prepared from PMMA" indicates the above preparation method. On the other hand, "in situ polymerization" indicates that all were prepared using a pregel solution.

[0132] In addition, in Table 1, "-" in the crosslinking agent column indicates that no crosslinking agent was used. The content of EGDMA is expressed as mol % relative to the content of the radical polymerizable compound.

[0133] [Table 1]

[0134] Table 2 shows the composition of the ion gels prepared from the pre-gel solutions in Table 1. The values ​​in the column for conversion rate show the conversion rate of the radical polymerizable compound when the ion gel was prepared by "in situ polymerization." "-" in Example 2 indicates that no data is available due to a different production method, and "-" in Comparative Example 3 indicates that the data could not be measured.

[0135] [Table 2]

[0136] Table 3 shows the results of the tensile test (breaking stress and self-repair rate) for each film. The self-repair rate for Comparative Example 3 is marked "-" because the cut test pieces did not bond, and therefore the test was not possible, indicating that the film had no self-repairing ability at all.

[0137] [Table 3]

[0138] From the results in Tables 1 to 3, the number average molecular weight is 5.0 × 105 ~1.0×10 7 It was found that films 1 to 5 obtained using a coating composition containing a polymer compound represented by the formula (I), an ionic liquid, and a solvent, and in which the mass ratio of the polymer compound content to the ionic liquid content is 0.15 or more and less than 1.00, have excellent strength and excellent self-repairing performance.

[0139] On the other hand, the number average molecular weight is 5.0×10 5 Film C1, which is less than 100 mm thick, had self-repairing ability but was insufficient in strength. Furthermore, film C2, in which the ratio of the polymer compound content to the ionic liquid content on a mass basis was 1.00, had a certain degree of strength but was insufficient in terms of self-repair performance. Furthermore, film C3, in which the molecular weight of the polymer compound could not be measured, had a certain degree of strength but no self-repairing ability at all.

[0140] In addition, the number average molecular weight of the polymer compound is 1.4 × 10 6 As described above, Film 1 had superior self-repairing performance compared to Film 2.

[0141] Furthermore, compared to Membrane 3, Membrane 1, in which the ratio of the polymer compound content to the ionic liquid content on a mass basis was 0.65 or less, had superior self-repairing performance.

[0142] The ionic liquid is represented by formula 8, and R 83 , and R 84 Membrane 1, in which is a trifluoromethyl group, had better self-repairing performance compared to membrane 4. [Industrial Applicability]

[0143] The laminate according to the embodiment of the present invention can be used as an easy-to-maintain exterior wall material, etc., because the coating film formed on the substrate has both excellent self-repairing properties and excellent strength. In addition, the laminate has an antistatic function due to the ionic liquid, and can be used as a more reliable antistatic coated substrate, combined with the excellent self-repairing performance.

Claims

1. Number average molecular weight is 5.0 x 10 5 ~1.0 x 10 7 A polymer compound having the formula: An ionic liquid; a solvent; a ratio of the content of the polymer compound to the content of the ionic liquid based on mass is 0.15 or more and less than 1.00; the polymer compound is poly(meth)acrylic acid or poly(meth)acrylic acid ester, The coating composition, wherein the ionic liquid is an ionic liquid represented by the following formula 8: 【Chemistry 1】 (In formula 8, R 81 and R 82 each independently represent an alkyl group having 1 to 10 carbon atoms, and R 83 and R 84 each independently represent a monovalent organic group.)

2. The number average molecular weight is 1.4×10 6 The coating composition according to claim 1 .

3. 3. The coating composition according to claim 1, wherein the ratio is 0.65 or less.

4. The coating composition according to any one of claims 1 to 3, wherein the polymer compound is polymethacrylic acid or a polymethacrylic acid ester.

5. R in the above formula 8 83 , and R 84 The coating composition according to any one of claims 1 to 4, wherein each of the is independently a perfluoroalkyl group.

6. In the above formula 8, R 83 , and R 84 The coating composition according to claim 5 , wherein is a trifluoromethyl group.

7. The coating composition according to any one of claims 1 to 6, wherein the solvent is at least one solvent selected from the group consisting of ketone-based solvents, aromatic hydrocarbon-based solvents, halogen-based solvents, and ether-based solvents.

8. 8. The coating composition according to claim 7, wherein the solvent is at least one solvent selected from the group consisting of acetone, toluene, chloroform, dichloromethane, and tetrahydrofuran.

9. A film formed from the coating composition according to any one of claims 1 to 8.

10. A laminate comprising a substrate and the film of claim 9 formed on the substrate.

Citation Information

Patent Citations

  • Composition for antistatic coating

    JP2009013198A

  • Hard coat film forming composition and hard coat film, and plastic substrate with hard coat film

    JP2014189596A

  • Pressure-sensitive adhesive sheet and optical member

    JP2015030770A

  • Composite film

    JP2015077786A

  • Addition polymer for electrodepositable coating compositions

    US20200407587A1